Combination of cellulose tissue paper and bleach-treated graphene in stiffness reinforcement of polyvinyl alcohol film - Abdullahb, Abu Hannifa; Ismail, Zulhelmi; W. Idris, Wan Farhana; Ahmad Khusairi, Zulsyazwan; Mohd Zuhan, Mohd Khairul Nizam (Elsevier, 2023)
A pre-treatment of graphene with bleach is considered one of the possible purification methods after liquid-phase exfoliation. However, the effect of this treatment on the mechanical reinforcement strategy for polymer film is yet to be investigated to date. In this full work, the influence of the C/O ratio, ID/IG, and volume of graphene after combination with cellulose tissue on the resulting stiffness of polyvinyl alcohol (PVA) composite film has been extensively studied. It is noticed that the incorporation of 30 ml graphene that had been pre-treated for 3 h into PVA had produced the best increment in elastic modulus (1.6 GPa against 0.4 GPa) while a shorter pre-treatment duration of graphene (1 h) would require more graphene volume (40 ml) to match the previous stiffness improvement level. By using the collected experimental data (90 samples), we further modeled the effect of tissue and PVA mass, C/O ratio, ID/IG, and graphene volume on modulus using machine learning (ML) algorithms.